The Ohio COVID-19 Survey: Preliminary Findings and Their Use During the Pandemic - Lisa A. Frazier; Eric Seiber; Kristin J. Harlow; Selasi Attipoe; Brian O'Rourke; Ohio COVID-19 Survey Team (Ohio Journal of Public Health, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has created exceptional health and economic uncertainty for Ohioans in 2020. In the spring of 2020, the state commissioned the Ohio COVID-19 Survey (OCS) to ask residential Ohio adults about how the pandemic was affecting them. The purpose of this research is to provide state leadership with real-time information about the effects of the pandemic and concurrent recession on Ohio households. Methods: The OCS is a special supplement to the Ohio Medicaid Assessment Survey (OMAS), a stratified random digit dial, cell phone and landline telephone survey. This study includes data collected weekly between April 20, 2020, and August 24, 2020. We conducted descriptive time-series analysis of the survey data and provided updates to the state's COVID-19 Response Team throughout the survey period. Results: Preliminary findings from the OCS reflect 3 themes among respondents: 1) elevated levels of concern over health and household economics; 2) disproportionate effects that exacerbate existing inequities; and 3) majority adjustment to "new normal" and acceptance of public health guidelines . Conclusion: Preliminary findings indicate that groups that were struggling before the pandemic have faced the biggest challenges with regard to health and household economics since it began. Data from the OCS enabled us to provide real-time analysis to state leadership regarding Ohioans' experience during the first 6 months of the COVID-19 pandemic. Further analysis and integration of additional data will allow us to provide deeper insights as Ohio seeks to move into recovery.
Keywords: Ohio; COVID-19; Economic stress; Survey; Inequities